Multiple metals exposure and chromosome damage: Exploring the mediation effects of microRNAs and their potentials in lung carcinogenesis. (January 2019) - Chen, Weilin; Fu, Wenshan; Deng, Qifei; Li, Yangkai; Wang, Ke; Bai, Yansen; Wu, Xiulong; Li, Guyanan; Wang, Gege; Huang, Jiao; He, Meian; Zhang, Xiaomin; et al.
Abstract: Objective: This study aimed to investigate the associations of multiple metals with chromosome damage, and further explore the mediation roles of microRNAs (miRNAs) and their potentials in lung cancer. Methods: We determined the urinary levels of 23 metals, lymphocytic micronucleus (MN) frequency, and ten candidate miRNAs in plasma among 365 healthy workers. Poisson and linear regression models were conducted to analyze the associations of urinary metals with MN frequency and miRNAs, respectively. The mediation effects of miRNAs on the metal-MN frequency associations were assessed by causal mediation analysis. Additionally, the levels of effective metal and miRNAs were measured in 43 pair-wised tumor and normal lung tissues. Results: The urinary level of titanium was inversely associated with MN frequency after Bonferroni correction [frequency ratio (FR) and 95% confidence interval (95%CI) = 0.88 (0.82, 0.94), p = 5.0 × 10 −4 ]. A doubling in urinary titanium was associated with 14.72%–38.17% decrease in plasma miRNAs. After multiple comparison, miR-24-3p and miR-28-5p significantly mediated 24.8% (7.7%, 70.0%) and 20.4% (5.7%, 52.0%) of the association between titanium and MN frequency ( p mediation = 0.002 and 0.004, respectively). Besides, a doubling in titanium was associated with a separate 53.4% and 47.2% decreased miR-24-3p and miR-28-5p expression in normal lung tissues. Lower titanium but higher levels of miR-24-3p and miR-28-5p were shown in tumor than normal tissues of lung squamous cell carcinoma patients (all p < 0.05). Conclusions: Our study proposed the negative associations of titanium with chromosome damage and lung cancer, and highlighted the mediating roles of miR-24-3p and miR-28-5p. Further investigations are warranted to validate these associations and uncover the underlying mechanisms. Highlights: Increasing level of titanium in urine was inversely associated with MN frequency. Exposure to titanium was associated with lower miR-24-3p and miR-28-5p in plasma. miR-24-3p and miR-28-5p mediated the effect of titanium on MN frequency. Lower titanium but higher miR-24-3p and miR-28-5p were shown in lung tumor tissues. Titanium in urine/tissue is related to miRNA that may be implicated in lung cancer.